Evaluasi Kualitas Sistem Informasi Penelusuran Perkara (SIPP) Di Pengadilan Negeri Salatiga Berbasis ISO/IEC 25010 - Giovano Keigo Lengkong; Endang Haryani (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2026)
This research aims to evaluate the quality of the Sistem Informasi Penelusuran Perkara (SIPP) at the Salatiga District Court, based on the ISO/IEC 25010: Product Quality Model. The urgency of this study is driven by its national implementation by the government and the high expectations of those seeking justice in this system as a transparent, effective, and accountable public service. The evaluation applied the ISO/IEC 25010 standard through a survey of 82 users. This study concluded that the SIPP application was considered to be of good quality, with an average quality score for 8 variables of 3.959. The highest quality aspects of SIPP were functional suitability (4.228) and portability (4.126), where the system features were adequate and complete, and it had good portability. The lowest quality aspect of SIPP was security (3.776). Although the quality of SIPP is obvious in the completeness of the features provided and its ability to run on various devices, the aspects of system modularity and access restriction mechanisms still need to be improved. Therefore, the recommendation for developers is to make improvements and enhancements in its security, particularly authentication mechanisms, as well as its periodic maintainability, in terms of system stability and performance.